The multifaceted interactions between Newcastle disease virus proteins and host proteins: a systematic review - Xiaolong Lu; Xiaoquan Wang; Xiufan Liu; Xiaowen Liu (Virulence, 2024)
Newcastle disease virus (NDV) typically induces severe illness in poultry and results in significant economic losses for the worldwide poultry sector. NDV, an RNA virus with a single-stranded negative-sense genome, is susceptible to mutation and immune evasion during viral transmission, thus imposing enormous challenges to avian health and poultry production. NDV is composed of six structural proteins and two nonstructural proteins that exert pivotal roles in viral infection and antiviral responses by interacting with host proteins. Nowadays, there is a particular focus on the mechanisms of virus-host protein interactions in NDV research, yet a comprehensive overview of such research is still lacking. Herein, we briefly summarize the mechanisms regarding the effects of virus-host protein interaction on viral infection, pathogenesis, and host immune responses. This review can not only enhance the present comprehension of the mechanism underlying NDV and host interplay, but also furnish a point of reference for the advancement of antiviral measures.